Enhancement of Dissolution Profile of Poorly Water Soluble Loratadine by Solid Dispersion Technique (Dhaka University Journal of Pharmaceutical Sciences, 2017)
This study was carried out to improve the dissolution properties of loratadine by solid dispersion technique. A series of solid dispersions of loratadine in PVP K-30 (1:1, 1:3 and 1:5) were prepared by kneading technique. The prepared solid dispersions were characterized by various physicochemical properties (fourier transform infrared spectroscopy, X-ray diffraction and scanning electron microscopy) and the dissolution characteristics were compared with loratadine and the physical mixtures of loratadine. It was revealed from the physicochemical analyses that there was a good compatibility between drug and carrier. On the other hand, the drug release from the prepared binary solid dispersions was significantly enhanced in comparison to both drug alone and the physical mixtures. Finally solid dispersion of loratadine: PVP K-30 prepared as 1:5 ratio was found to be described by non-Fickian release mechanism and was selected as the best formulation in this study.Dhaka Univ. J. Pharm. Sci. 15(2): 195-201, 2016 (December)